2015
DOI: 10.1093/femsyr/fov077
|View full text |Cite
|
Sign up to set email alerts
|

PolymicrobialCandidabiofilms: friends and foe in the oral cavity

Abstract: The role of polymicrobial biofilm infections in medicine is becoming more apparent. Increasing number of microbiome studies and deep sequencing has enabled us to develop a greater understanding of how positive and negative microbial interactions influence disease outcomes. An environment where this is particularly pertinent is within the oral cavity, a rich and diverse ecosystem inhabited by both bacteria and yeasts, which collectively occupy and coexist within various niches as biofilm communities. Studies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 171 publications
0
71
0
1
Order By: Relevance
“…Transcriptional analyses revealed that key adhesins were negatively impacted whereas genes associated with aggregation were positively impacted. Collectively, these data demonstrate that CUR has the potential to be used in denture care as a means of preventing denture-induced stomatitis, a disease associated with C. albicans biofilms (O'Donnell et al, 2015a). …”
Section: Discussionmentioning
confidence: 92%
“…Transcriptional analyses revealed that key adhesins were negatively impacted whereas genes associated with aggregation were positively impacted. Collectively, these data demonstrate that CUR has the potential to be used in denture care as a means of preventing denture-induced stomatitis, a disease associated with C. albicans biofilms (O'Donnell et al, 2015a). …”
Section: Discussionmentioning
confidence: 92%
“…Broad spectrum activity that includes activity against Gram-positive and Gram-negative bacteria and fungi is important because mixed infections are common in oral cavity causing topical and postsurgery infections. 49 Moreover, significant reduction of fungal biofilm growth and prevention before penetration into dental filling has been observed. Importantly, in agreement with previous reports, we confirmed that magnetic derivatives of CHX not only maintained the antimicrobial activity of CHX but also increased its killing properties in the presence of saliva.…”
mentioning
confidence: 99%
“…This is likely influenced by the diverse microbiota in this environment, which we have recently described (22). Indeed, there is increasing evidence that Candida and bacteria form polymicrobial biofilms, and that some bacterial species common to the oral cavity can enhance the pathogenicity of C. albicans (35)(36)(37)(38), and that the presence of specific oral bacteria is enough to transform a C. albicans LBF into a HBF (39). We have also reported a significant association between lactobacilli and yeasts in this context, and this may be more important than C. albicans alone, as is the perceived paradigm for this DS.…”
Section: Discussionmentioning
confidence: 82%